Synthesis and characterization of layered double hydroxide as biocompatible materials / Yamin Yasin and Nur Mushirah Ismail - Yasin, Yamin; Ismail, Nur Mushirah (Research Management Institute (RMI), 2011)
The continuous development of new drug delivery systems is driven by the need to maximize therapeutic activity while minimizing negative side effects. Recently, more attention is given to LDHs containing drug molecules due to its unique properties such as enhanced dissolution property, increased thermal stability and control the drug release. LDH is one class of drug delivery vehicle that has received more attention because it can accommodate polar organic compounds between their layers and form a variety of intercalated compounds. Intercalation compounds with biologically active species could thus provide composites with ability to control the drug release. Hydrotalcite-like compounds based on Mg and Al hydroxycarbonates are the most suitable layered host because of their biocompatibility and because there are already used in their medicine as antiacid and antipepsin activity [4]. Because the release of drugs is potentially controllable, these new drug-inorganic composite have a great potential as a delivery host in the pharmaceutical field in preparing a controlled release formulation. Layered double hydroxides (LDHs), also called anionic clays, displays unique physical and chemical properties surprisingly close to the properties of clay minerals. Layered double hydroxides are group of inorganic materials which can be used as biocompatible materials or as host compounds. LDHs are layered solids having positively charged layers and interlayer charge compensating anions. The chemical composition of LDHs can be represented by the general formula [M"^-x; M111 (OH)2]x+ Az"x/z • yH20 or [M1 M2 in (OH)2]+ Az'1/Z . yH20 where M1, M" and Mm are mono, di- and trivalent cations, respectively, occupying octahedral positions in hydroxide layers, and Az" is an interlayer charge-compensating anion. Lawsone (Law) [2-hydroxy-1,4-naphtaquinone] is a red orange dye present in the leaves of henna plant Human have used henna extracts containing lawsone as hair and skin pigments for many years. Lawsone strongly absorbs UV light and aqueous extracts can be effective sunless tanning sunscreens. Nowadays, lawsone is becoming more and more popular due to its profound effect on human health. In the present study, lawsone was selected as biological active species and intercalated into Zn and Al layered double hydroxides by both co-precipitation and ion exchange techniques. The study focuses on the intercalation structure through characterizations of intercalation compound by using Powder X-ray diffraction (PXRD), Fourier transform infrared (FTIR) and TG-DTA analysis.